ISOLASI DAN IDENTIFIKASI SENYAWA YANG BERPOTENSI SEBAGAI ANTITUMOR PADA DAGING BUAH PARE (Momordica charantia L.) - Susanah Rita, Wiwik; Suirta, I W.; Sabikin, Ali (Jurnal Kimia (Journal of Chemistry), 2012)
Isolation and identification of the compound which has a potency as antitumor from bitter melon have been carried out. Extraction was conducted n-hexane, chloroform, and ethanol respectively using each extracts obtained were examined with brine shrimp lethality test. The most toxic extract was ethanol extract (LC50 223 ppm). Separation and purification of the compounds from the ethanol extract were conducted by column chromatogaraphy using a gel silica 60 as the stationary phase and benzene : acetic acid ( 8:2) as the mobile phase. This yielded 3 fractions. Then the fractions were examined with brine shrimp lethality test and the most toxic fraction was found to be the fraction 1 (LC50 31,62 ppm), but the fraction that was analysed further was fraction 3 (LC50 100 ppm), because fraction 1 consists of using compounds that were difficult to separate. The purity fraction 3 was tested conducted thin layer chromatography and its activity as antitumor agent was tested using Agrobacterium tumefacien A-208. The test was in 6 weeks and that fraction 3 has a potency as an antitumor agent at 1000 ppm. The identification with gas chromatography – mass spectroscopy indicate that the antitumor isolate from bitter melon contains 3 mayor compoundsnamely dioxtyl hexadioate esther, palmitic acid, stearic acid.
Keywords: antitumor, bitter melon, Artemia salina L., Agrobacterium tumefaciens A-208